Autism spectrum disorders in adolescents and adults evidence-based and promising interventions - Tincani, Matt; Bondy, Andy (New York The Guilford Press, 2014)
"We've edited this collection of chapters on evidence-based and promising practices for adults with ASD. During the past 25 years or so there has been a concomitant increase in research and publications regarding the identification, assessment, and education of these children. This heavy focus of on children is understandable given the promise of early identification and intervention. However, there remains a paucity of research and guidelines that focus on the issues that face adults with ASD. We asked a number of the leading researchers to write chapters on critical issues related to the well-being of adults with ASD. Each set of authors was asked to review the current literature associated with a wide array of topics. In addition to reviewing key research, each chapter provides some examples of how specific features and strategies may influence a hypothetical case in terms of practical decision making"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Autism spectrum disorders in children -- Treatment; Autism spectrum disorders -- Treatment